An Error-Resilient Arithmetic Coding Algorithm for Compressed Meshes - Zhi-Quan Cheng; Bao Li; Kai Xu; Yan-Zhen Wang; Gang Dang; Shi-Yao Jin (2008 International Conference on Cyberworlds : 22-24 September 2008, 2008)
The effort of on-the-fly accessing 3D contents over the Internet has been done in recent years. And 3D streaming has been investigated to represent 3D models in the compact format and progressively transmit them on the limited-bandwidth and lossy channel. In the paper, an error resilient 3D mesh coding algorithm is presented, which employs an extended multiple quantization (EMQ) arithmetic coder method, inspired by the error-resilient JPEG 2000 image coding standards. With periodic arithmetic coder restarting and termination markers, the error resilient EMQ coder divides bit stream into little independent parts and enables basic transmission error containment. Furthermore, the EMQ coder has the intrinsic capacity of handling noise by using the maximum a posteriori (MAP) decoder. Experiments show that the method improves the mesh transmission quality in a simulated network environment.